2019
DOI: 10.1590/1982-0224-20190075
|View full text |Cite
|
Sign up to set email alerts
|

Molecular assessment of Gymnotus spp. (Gymnotiformes: Gymnotidae) fishing used as live baitfish in the Tietê River, Brazil

Abstract: The capture of live bait for sport fishing is an important activity for fishing communities. The main species used for this purpose are members of the genus Gymnotus, which comprises numerous species of cryptic nature that are difficult to identify based on external morphology. The aims of this work were to identify through partial sequences of the COI gene Gymnotus species fished in the Jacaré-Guaçu River, SP, and to develop a molecular diagnostic approach using PCR-RFLP to identify these species. Partial COI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Quantitative morphometric and multilocus genetic data sets have now been developed to study geographic variation within and among closely related species in many NFF taxa (e.g., Crampton et al 2016, Melo et al 2016a, Silva et al 2016, Craig et al 2017, Burress et al 2018b). These data sets have been used to delimit species boundaries (e.g., Bagley et al 2015, Faria-Pereira et al 2019, Serrano et al 2019 and to identify cryptic and pseudocryptic species (e.g., Melo et al 2016b). The emerging use of genome-wide markers [e.g., ultraconserved elements (UCEs), restriction site-associated DNA sequencing (RADseq) markers] has expanded the number of loci used in phylogenetic and phylogeographic analyses of NFF taxa into the thousands (Chakrabarty et al 2017, Alda et al 2018, Roxo et al 2019.…”
Section: Biodiversity Dimensionsmentioning
confidence: 99%
“…Quantitative morphometric and multilocus genetic data sets have now been developed to study geographic variation within and among closely related species in many NFF taxa (e.g., Crampton et al 2016, Melo et al 2016a, Silva et al 2016, Craig et al 2017, Burress et al 2018b). These data sets have been used to delimit species boundaries (e.g., Bagley et al 2015, Faria-Pereira et al 2019, Serrano et al 2019 and to identify cryptic and pseudocryptic species (e.g., Melo et al 2016b). The emerging use of genome-wide markers [e.g., ultraconserved elements (UCEs), restriction site-associated DNA sequencing (RADseq) markers] has expanded the number of loci used in phylogenetic and phylogeographic analyses of NFF taxa into the thousands (Chakrabarty et al 2017, Alda et al 2018, Roxo et al 2019.…”
Section: Biodiversity Dimensionsmentioning
confidence: 99%
“…29 It thus seems likely that many studies have analyzed different species, identified erroneously as G. carapo, generating parameters distinct from those expected to represent a single species. Inconsistencies have already been reported in the regulation of Gymnotus species harvested for live bait, such as the fact that the legislation refers only to G. carapo in the Tietê River (Paraná basin), whereas Faria-Pereira et al 69 had identified only Gymnotus cf. sylvius and Gymnotus cf.…”
Section: Discussionmentioning
confidence: 99%
“…DNA barcode has been proved to be a helpful tool in identifying species through the analysis of short samples of mtDNA, with several applications (DeSalle & Goldstein, 2019). These are especially important when entire specimens are not available or not properly preserved for morphological identification, as exemplified by old or badly preserved type specimens (Silva et al, 2017(Silva et al, , 2019, in the analysis of ecological interactions of predators or parasites through the analysis of stomach contents (Amundsen & Sánchez-Hernández, 2019;Bonato et al, 2018;Kress et al, 2015), and forensic or monitoring programme of fish explored for food or other purposes (Carvalho et al, 2017;Faria-Pereira et al, 2019). It has also been demonstrated relevant in the detection of morphologically similar cryptic species (DeSalle & Goldstein, 2019;Waugh, 2016).…”
Section: Ecological Notesmentioning
confidence: 99%